Nothing Exists, or the Problem of Being in the Thinking of Sophists - Jankauskas, Skirmantas (Problemos, 2003)
The paper deals with an impact of ideas of Sophists in the early Greek philosophy. The ideas of the two most famous Sophists Gorgias and Protagoras are discussed. The analysis is carried out on the assump- tion that the movement of Sophists should be tre- ated as a new and relatively autonomous social phe- nomenon that needs to be legalized in the Greek cosmos. An attempt is made to demonstrate that the Sophists got involved in philosophical discussions with an intent to establish an ontological niche in the Greek cosmos. From this standpoint is analyzed the work of Gorgias „On Nature, ar the N0n-ex1'stent“. In the course of this analysis it is shown that the argu- ments of the previous Greek philosophers, especially those of Eleatics, are logically counter-posed and thus discredited. It is inferred that Gorgias in this way complicated „naive“ or unproblematic thinking of the Greek philosophers, and concurrently identified, though only in a negative aspect, the fundamen- tal premise of the Sophistic movement - the signi- ficance of individual opinion. Finally, it is argued here that Protagoras' famous criterion of man-mea- sure defmes the same premise in a positive manner. lt also is demonstrated that the essence of the cri- terion consists in the sensual measuring of the cos- mos (logos). This kind of measuring deprives the cosmos of its traditional meanings and values, and by the same virtue makes language a relativer autono- mous phenomenon. This, in its turn, makes the fun- damental part of the sophistic activity - the rhetoric - possible. The paper concludes with the conclusion that the Sophists endowed the Greek philosophy with three fundamental problems - axiological, ontological and gnoseological.
Keywords: early Greek philosophy; Sophists; being; knowledge; man-measure; rhetoric